Popliteal vein aneurysm: Is it necessary to apply anticoagulants after a surgery? - Geremek, M.; Trochimczuk, M.; Janik, M.; Malek, G.; Ostrowski, K. (Phlebologie, 2014)
Aim: This study is intended to evaluate indications for antithrombotic therapy in patients with tangentially resected popliteal vein aneurysm.Methods: Evaluation of the course of therapy in a patient with popliteal vein aneurysm. Literature review covered literature data published within the last decade. Studies were identified by searching Medline and PubMed databases for the following phrases: ”popliteal venous aneurysm” and ”popliteal vein aneurysm”.Results: The case study and literature review revealed that thromboembolic risk cannot be entirely eliminated by means of tangential resection of popliteal vein aneurysm. Vein suture and residual postoperative dilatation of the popliteal vein can be considered predisposing factors to thromboembolic complications.Conclusion: Patients with tangentially resected popliteal vein aneurysm involving vein suture can be administered oral antithrombotic therapy within three months postoperatively. Therapy extension should be made conditional on the degree of vein dilation reduction. Where the diameter at surgical site is larger than 20 mm, it appears appropriate to continue antithrombotic therapy and to repeat assessment in six months time.
Keywords: Popliteal vein aneurysm; venous thromboembolism; antithrombotic therapy; tangential resection